Uma investigação sobre tendências metodológicas da educação matemática a partir das formações continuadas (Sergipe, 1988 a 2006) - Santos, Rone Peterson Oliveira (2012)
This article presents the results of a survey about the continuum education provided by the managers of the school from the state of Sergipe who thought Mathematics from 1988 2006. The aim of this research was to analyze whether and how the methodological trends of Mathematics Education were approached in these formation. To achieve this purpose, it was necessary, initially, the identification of the works concerned to the theme, collection of documents, such as certificates and planning, in the file of Centro de Qualificação de Pessoal Professor Antônio Garcia Filho and interviews with teachers, who were trainers at that time. As theoretical basement, it was consulted Valente (2007). In order to understand the terminology about the formation, it was adopted Marin (1995), Destro (1995), Hypollito (2000), Nacarato (2000). To understand about the methodological trends and Mathematics Education it was made use of D Ambrósio (1989), Mendes (2009), Fiorentini and Lorenzato (2007). From the data, besides the identification of the contents, terminology, timing of realization and teachers, it was possible to characterize the proposals of the continuum formation in Sergipe which can be categorized into two groups. The first one, linked to the Central Nucleus of Mathematics (1988-1996), were formations organized by Mathematics teachers who held meetings with educational character and also ministered courses , lectures and workshops for the colleagues. The second group, linked to the School Development Program (2001-2007), were formations performed by professionals linked to consulting firms which approached themes according to specific demands of each school. Regarding to the methodological trends, it s possible to say that, in the formations of the first group, there are explicit references to the Mathematics Education and to the methodological trends. However, trough the examination of the activities it s possible to say that they were not approached in a way that can be considered as a methodology, but as a resource to make the class different. The second group presents a dispersed theme and there is no highlight to the solving problems, the mathematical games, the history of mathematics, the use of technology and the ethno mathematics. In other words, to the second period analyzed, it is possible to say that, in the late 80s, of the twentieth century, had a greater enthusiasm with themes related to what was called methodological trends in mathematics education, but they were not worked as a methodology, but as a resource to teach different math classes.